Case Report: Event-Related Desynchronization Observed During Volitional Swallow by Electroencephalography Recordings in ALS Patients With Dysphagia - Ogawa, Akari; Koganemaru, Satoko; Takahashi, Toshimitsu; Takemura, Yuu; Irisawa, Hiroshi; Matsuhashi, Masao; Mima, Tatsuya; Mizushima, Takashi; Kansaku, Kenji (Frontiers in Behavioral Neuroscience, 2022)
Dysphasia is a severe disability affecting daily life in patients with amyotrophic lateral sclerosis (ALS). It is caused by degeneration of both the bulbar motor neurons and cortical motoneurons projecting to the oropharyngeal areas. ALS patients with dysphagia often show a longer duration of more than several seconds during volitional swallowing, possibly due to weakened motor outputs. However, there have been no reports on the time course and distribution of brain activity during prolonged swallowing in these patients. In this case report, we investigated the time course and distribution of event-related desynchronization (ERD) and corticomuscular coherence (CMC) during volitional swallow using electroencephalography (EEG) with 32 electrodes in two patients with ALS. Case 1 (a 71-year-old man) was diagnosed 2 years before the evaluation. His first symptom was muscle weakness in the right hand; 5 months after the first symptom, dysphagia developed and exacerbated. Since his dietary intake decreased, he was given an implantable venous access port for nutrition intake. Case 2 (a 64-year-old woman) was diagnosed 1 year before the evaluation. Her first symptom was open-nasal voice and dysarthria; 3 months after the first symptom, dysphagia developed and exacerbated. The patient was given a percutaneous endoscopic gastrostomy for nutrition intake. EEG recordings were performed during volitional swallowing, and the ERD was calculated. The average swallow durations were 7.6 ± 3.0 s in Case 1 and 8.3 ± 2.9 s in Case 2. The ERD was localized in the prefrontal and lateral sensorimotor areas and lasted from a few seconds after the initiation of swallowing to the end in Case 1. The ERD was localized in the lateral sensorimotor areas at the initiation of swallowing and disappeared before the pharyngeal phase in Case 2. CMC was not observed in either case. These results suggest that compensatory processes for cortical motor outputs might depend on individual patients and that an effective therapeutic approach could be investigated according to the individuality of ALS patients with dysphagia.